The Illusion of Risk Control: What Does it Take to Live With Uncertainty? - Gilles Motet (SpringerBriefs in Applied Sciences and Technology, 2017)
This book explores the implications of acknowledging uncertainty and black swans for regulation of high-hazard technologies, for stakeholder acceptability of potentially hazardous activities and for risk governance. The conventional approach to risk assessment, which combines the likelihood of an event and the severity of its consequences, is poorly suited to situations where uncertainty and ambiguity are prominent features of the risk landscape. The new definition of risk used by ISO, "the effect of uncertainty on [achievement of] one's objectives", recognizes this paradigm change. What lessons can we draw from the management of fire hazards in Edo-era Japan? Are there situations in which increasing uncertainty allows more effective safety management? How should society address the risk of potentially planet-destroying scientific experiments? This book presents insights from leading scholars in different disciplines to challenge current risk governance and safety management practice.